Histological characteristics of hair follicles at different hair cycle and in vitro modeling of hair follicle-associated cells of yak (Bos grunniens) - Liao, Bo; Cui, Yan; Yu, Sijiu; He, Junfeng; Yang, Xue; Zou, Shengnan; Li, Sijie; Zhao, Pengfei; Xu, Hongwei; Long, Min; Wang, Xiaoyan (Frontiers in Veterinary Science, 2023)
To adapt to the extreme conditions of plateau environments, yaks have evolved thick hair, making them an ideal model for investigating the mechanisms involved in hair growth. We can gain valuable insights into how hair follicles develop and their cyclic growth in challenging environments by studying yaks. However, the lack of essential data on yak hair follicle histology and the absence of in vitro cell models for hair follicles serve as a limitation to such research objectives. In this study, we investigated the structure of skin tissue during different hair follicle cycles using the yak model. Additionally, we successfully established in vitro models of hair follicleassociated cells derived from yak skin, including dermal papilla cells (DPCs), preadipocytes, and fibroblasts. We optimized the microdissection technique for DPCs culture by simplifying the procedure and reducing the time required. Furthermore, we improved the methodology used to differentiate yak preadipocytes into mature adipocytes, thus increasing the differentiation efficiency. The introduction of yak as a natural model provides valuable research resources for exploring the mechanisms of 2 hair growth and contributes to a deeper understanding of hair follicle biology and the development of regenerative medicine strategies.